Rebar corrosion in mortars with high limestone filler content - Batic, O. R. (2013)
Purpose – This research aims to study the influence of limestone filler on rebar corrosion. Design/methodology/approach – Mortar samples containing 35% calcareous filler and with a rebar inserted in the axis, were cast. Specimens were cured at the open air and during 28 days in lime water. After curing, they were submerged in two electrolytes (tap water and 3% NaCl) and corrosion parameters (corrosion potential and corrosion current) were monitored over time by d.c. techniques. Simultaneously, electrochemical noise measurements were carried out. After corrosion tests, rebars were pulled out by lateral compression, and their surface observed by scanning electron microscopy. Findings – In general, carbonate additions impaired mortar protective properties, especially in the presence of chloride and changed the nature of the protective layer on rebars. The curing process did not introduce significant differences except for mortars with a high water cement ratio cured in lime water for which the beneficial effects of the simultaneous presence of carbonate and lime in the pore solution could be appreciated. The role of carbonate additions is to provide carbonate anions to passivate rebars. This passivation process caused corrosion rates not to be so high. Carbonate anions also deposited on oxide spots which were rendered passive but this process was not uniform. Certain areas on the rebar underwent intense carbonation while others showed increased corrosion rates. Originality/value – There are not many corrosion studies about the influence of limestone filler on rebars corrosion. Particularly, this paper deals with mortars containing high percentages of carbonate additions. Results showed that the presence of this type of admixture changes the structure of the passive layer and, sometimes, may increase corrosion rates.